Cardioprotective Role of SIRT5 in Response to Acute Ischemia Through a Novel Liver-Cardiac Crosstalk Mechanism - Zhou, Boda; Xiao, Min; Hu, Hao; Pei, Xiaoxia; Xue, Yajun; Miao, Guobin; Wang, Jifeng; Li, Wanqi; Du, Yipeng; Zhang, Ping; Wei, Taotao (Frontiers in Cell and Developmental Biology, 2021)
Protein posttranslational modifications play important roles in cardiovascular diseases. The authors’ previous report showed that the abundance of succinylated and glutarylated proteins was significantly lower in the serum of patients with acute myocardial infarction (AMI) than in that of healthy volunteers, suggesting a potential relationship between protein acylation and AMI. Sirtuin 5 (SIRT5) facilitates the removal of malonyl, succinyl, and glutaryl modification; however, its effects on AMI remain unknown. In this study, the levels of SIRT5 in AMI mouse model was compared. Results showed elevated hepatic SIRT5 after myocardial infarction. Hepatocyte-specific SIRT5 overexpressing mice (liver SIRT5 OE) were generated to address the possible involvement of hepatic SIRT5 in AMI. The areas of myocardial infarction, myocardial fibrosis, and cardiac function in a model of experimental myocardial infarction were compared between liver SIRT5 OE mice and wild-type (WT) mice. The liver SIRT5 OE mice showed a significantly smaller area of myocardial infarction and myocardial fibrosis than the WT mice. The fibroblast growth factor 21 (FGF21) in the blood and myocardium of liver SIRT5 OE mice after AMI was markedly elevated compared with that in WT mice. The results of mass spectrometry showed increased levels of proteins regulating tricarboxylic acid cycle, oxidative phosphorylation, and fatty acid -oxidation pathways in the liver mitochondria of liver SIRT5 OE mice. These findings showed that SIRT5 may exhibit a cardioprotective effect in response to acute ischemia through a liver-cardiac crosstalk mechanism, probably by increasing the secretion of FGF21 and the improvement of energy metabolism.